A systematic review of the methods and drugs used for performing suprascapular nerve block injections for the non-surgical management of chronic shoulder pain. Issue 4 (November 2021) - Smith, Neil; Liew, Ziheng; Johnson, Samantha; Ellard, David R; Underwood, Martin; Kearney, Rebecca
Suprascapular nerve block (SSNB) injections are growing in popularity as a treatment option for people with chronic shoulder pain. The optimal method of injection and aftercare is unknown. This review describes the current methods and drugs used for performing SSNB injections in the non-surgical management of adults with chronic shoulder pain in order to inform future research in this area. Systematic searches of CINAHL, MEDLINE (OVID), AMED, Embase databases and the Cochrane Library were undertaken from inception to June 2020. Data on the method and drugs used for injection and aftercare were extracted and summarised for areas of commonality and discrepancy. We included 53 studies in this review. In total, eight different injection methods were reported within the included studies. Indirect surface land-marked methods were the most common method reported in 21 studies. Direct surface land-marked methods were reported in 12 studies. Ultrasound-guided methods used alone were reported in 16 studies. Both fluoroscopy and computed tomography methods used alone were reported in one study each. Electromyography was used in combination with other injection methods in nine studies. Wide variation in the composition of the injectate was observed between studies. Local anaesthetic was used within injectate preparations in all studies. Local anaesthetic used alone was reported in 20 studies, combined with steroid in 29 studies and combined with various other components in 5 studies. Physiotherapy following injection was reported in 26 studies. Reported details of physiotherapy varied considerably. This review identified substantial variation in the methods and drugs used to perform SSNB injection in clinical trials. Current literature demonstrates a wide range of methods used for SSNB injection administration. Consensus research defining standardised practice for SSNB injection is now needed to guide future clinical practice and research.